Modeling of thermophysical processes with moderate cryogenic effect on the periodontal zone using a thermoelectric cooling system - O. V. Evdulov; S. G. Magomedova; E. A. Dzhabrailova (LLC "Endo Press", 2020)
The aim of the article is to develop a mathematical model and conduct a numerical experiment of a thermoelectric system (TPP) for the treatment of in^ammatory periodontal diseases by moderate cryotherapy.Materials and methods. A design, a physical and mathematical model of TES for the treatment of in^ammatory periodontal diseases by moderate cryotherapy, developed on the basis of solving the unsteady heatconduction problem fora multilayer system, has been developed.Results. /4s a result of a numerical experiment, data were obtained that describe the temperature distribution over the thickness of each of the layers in the system, taking into accountthe heatfluxes on the junctions of the thermoelectric battery (ТЕБ), the parameters of the periodontal region, the temperature change atvarious points of the thermal power plant system - the periodontal region in time. It has been established that the necessary level of procedures associated with lowering the surface temperature of the periodontal zone to -40°C can be realized with a cooling capacity of ТЕБ of 6000 W/m2, which corresponds to the power of modern standard produced thermoelectric modules.Conclusions. It was estabished that the selection of the geometrical parameters TEB and power supply should be guided by the restrictions on the operation of the device, as well as medical norms and standards in order to avoid frostbite of adjacent tissues. A method for increasing the efficiency of the system is proposed, according to which the preliminary cooling of thermal power plants by an external source of cold is used, as well as by the use of forced operating modes of thermal fuel cells TEB.